The choice of teaching as a career - Evans, Hyacinth L. (1993)
This study sought to identify the reasons Jamaican teachers chose teaching as a career, and the main factors that influenced this choice. The sample consisted of all the 1,989 graduates of 10 teachers' colleges and departments in Jamaica. Data were obtained through the use of a questionnaire and in-depth interviews with a random sample of 20 respondents from 4 of the 14 parishes. The four reasons most frequently mentioned for choice of teaching relate to service or opportunity to contribute to society, love of or desire to work with children, love of teaching or the profession, and the influence of family members or teachers
Keywords: Career choice